The Human Respiratory Systems Learning Video: Validity and Feasibility - Wulandari, I Gusti Ayu Yusri; Surya Abadi, Ida Bagus Gede (International Journal of Elementary Education, 2021)
This research is motivated by the lack of availability of learning media in the form of learning videos during the COVID-19 pandemic, especially on the science content of the human respiratory system material. This study aims to describe the design and validity of the development of learning videos. This study uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The subjects in this study were content experts, learning design experts, learning media experts, and fifth grade elementary school students. The methods and instruments used to collect data in this study used a questionnaire. The data analysis technique used is descriptive qualitative analysis and descriptive quantitative analysis. The results of the analysis of the validity test obtained the following results. content experts got 87.5% results with good qualifications, learning design experts got 95.0% results with very good qualifications, learning media experts got 95.0% results with very good qualifications, and individual trials got 95.8 results % with very good qualifications. Thus, based on this analysis, it can be stated that this learning video product is valid and suitable for use in the science content of the human respiratory system material.